CREATIVE MARKETING STRATEGIES IMPLEMENTED IN ATTRACTING CONSUMER ATTENTION IN LEMANG BATOK BUSINESS TYPICAL TEBING TINGGI CITY - Hastuti Handayani Harahap (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2023)
This study aims to determine the Creative Marketing Strategy Applied in Attracting Consumer Attention (Case Study in the Lemang Batok Souvenirs Typical City of Tebing Tinggi). The implementation of creative marketing is very important considering that it has been stated that online media will greatly benefit because of the level of effectiveness and efficiency it promises. The development of creative marketing has seen rapid growth in income every year from before using online media and after using online media in its marketing strategy, the implementation of online media that has been carried out is in accordance with the benchmark: the application of creative marketing through online media to consumer buying interest, according to lemang shell business goals, they try to market their products to keep up with the times. The impact of implementing creative marketing has a positive impact, with a measure of achieving business goals, easy integration with other businesses, easy adaptation to the environment and businesses have a dependence on the use of online media, even implementing creative marketing does not have a negative impact seen from various aspects, this make an answer that successful creative marketing is applied as one of the marketing strategies for the lemang shell business in supporting the marketing of its products, of course this can also be developed by other typical food producers.